Stage beauty Qwerty Films, Artisan Entertainment presents a Tribeca production in association with N1 European Film Produktions GmbH & Co. KG, BBC Films and Artisan Entertainment, a Richard Eyre film ; produced by Robert De Niro, Jane Rosenthal, Hardy Justice ; screenplay by Jeffrey Hatcher ; directed by Richard Eyre. - Crudup, Billy, 1968-; Danes, Claire, 1979-; Everett, Rupert; Wilkinson, Tom, 1948-2023; Chaplin, Ben; Dunn, Andrew; Fenton, George., cmp; Hatcher, Jeffrey, 1957-; De Niro, Robert (Lions Gate Home Entertainment [Distributor], 2005)
"Welcome to the 17th century stage, where Ned Kynaston's performance of Desdemona in Shakespeare's 'Othello' brings the house down nightly. Ned is the "most beautiful woman on the London stage". That is, until the King renounces the royal edict that only men can play women on stage. Enter Maria, Ned's seemingly loyal dresser, who becomes an instant star, leaving Ned to suppress his ardent feminine traits and make a man of himself"